2018
DOI: 10.1103/physrevlett.120.033203
|View full text |Cite
|
Sign up to set email alerts
|

Electron Dynamics Driven by Light-Pulse Derivatives

Abstract: We demonstrate that ultrashort pulses carry the possibility for a new regime of light-matter interaction with nonadiabatic electron processes sensitive to the envelope derivative of the light pulse. A standard single pulse with its two peaks in the derivative separated by the width of the pulse acts in this regime like a traditional double pulse. The two ensuing nonadiabatic ionization bursts have slightly different ionization amplitudes. This difference is due to the redistribution of continuum electron energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…[4] and reference therein). For laser pulses at large photon energies and high intensities, the so-called "dynamic interference" in the atomic ionization has been theoretically observed [5][6][7][8][9][10][11][12][13][14]. It refers to the interference between two electronic wave packets respectively ejected in the rising and the falling edge of a laser pulse.…”
Section: Introductionmentioning
confidence: 99%
“…[4] and reference therein). For laser pulses at large photon energies and high intensities, the so-called "dynamic interference" in the atomic ionization has been theoretically observed [5][6][7][8][9][10][11][12][13][14]. It refers to the interference between two electronic wave packets respectively ejected in the rising and the falling edge of a laser pulse.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond cold physics, external fields are also used in ultrafast physics where short laser pulses probe photoionization processes [17]. In such systems the pulse envelope plays a crucial role since it induces a time-dependent AC-Stark shift of the energy levels of the system whereas the light-pulse derivatives yield a dynamic interference in photoionization cross-sections [18][19][20][21][22][23][24][25], [26].In this letter, the RF-induced association process in an ultracold thermal gas is investigated and it is shown that the RF field envelope plays a crucial role. This allows us to extend the concept of dynamical interference in strong field ionization into the realm of ultracold physics and to explore its impact on the production of cold molecules.…”
mentioning
confidence: 99%
“…Researches on different aspects of high-frequency-laser ionization scatter in references [25][26][27][28][29][30][31][32][33][34], for our purpose here, we summarize the main conclusions with a special emphasis on the role played by KH states. We expanded the oscillating Coulomb potential as [35,36].…”
mentioning
confidence: 99%
“…Z β0Ip < 1 implies the deformation of the wave function is significant. In stage C, the nonadiabatic ionization becomes more and more important [25][26][27]. There is no distinct boundary between B and C. The nonadiabatic coupling is determined by the product of N ∂ ∂β 0 M and ∂β 0 ∂t , which implies an envelope dependence.…”
mentioning
confidence: 99%